Il complotto interiore. Affrontare le nuove forme di alienazione - Lomartire, Alessandro (Filosofia, 2019)
Il Pendolo di Foucault was published in 1988, and was immediately available in every bookshop. The plot tells the story of an apparent universal conspiracy which then turns out to be only a great misunderstanding. Thirty years later we realize that the phenomenon of good plot for a novel has become more and more widespread, invading fields unimaginable until recent times such as politics and the intellectual community. But what is a conspiracy theory? What kind of people believe in it? How to face this rising phenomenon and its implications? Recent studies on conspiracy theory and the work of Castoriadis suggest an answer to all these questions: revitalizing Democracy and educating people to autonomy.